2020
DOI: 10.1111/cea.13711
|View full text |Cite
|
Sign up to set email alerts
|

Tree pollen exposure is associated with reduced lung function in children

Abstract: Allergic disease is a recognized global epidemic. 1 An increasing proportion of asthma can be classed as allergic asthma. 2 In children, asthma remains a significant cause of ill health, disability and poor quality of life. 3 Lung function and exhaled markers of airway inflammation are important measures of asthma activity and overall lung health. Identifying modifiable factors that influence these markers is important to understand asthma and for asthma control. The role of pollen in allergic respiratory dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 36 publications
2
18
0
1
Order By: Relevance
“…Our pattern of null findings related to %FEV 1 /FVC are notable, since asthma is an obstructive disease characterized by a reduced FEV 1 /FVC ratio. Our finding is similar to a study by Lambert et al [ 55 ] in which children exposed to pollen demonstrated similarly decreased FEV 1 and FVC, but no effect was observed on FEV 1 /FVC.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our pattern of null findings related to %FEV 1 /FVC are notable, since asthma is an obstructive disease characterized by a reduced FEV 1 /FVC ratio. Our finding is similar to a study by Lambert et al [ 55 ] in which children exposed to pollen demonstrated similarly decreased FEV 1 and FVC, but no effect was observed on FEV 1 /FVC.…”
Section: Discussionsupporting
confidence: 92%
“…This could be important for examining hypothesized relationships between child respiratory disease and exposure to aeroallergens such as pollen [ 34 ] or for detecting effect measure modification by atopy. For example, two recent studies have found grass pollen [ 63 ] and evergreen pollen [ 55 ] negatively associated with lung function in children and adolescents. Markevych et al [ 22 ] found that both asthma and allergic sensitivity increased as exposure to trees, and specifically allergenic trees, increased.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, we performed a data analysis of the MACS high-risk cohort which consisted of primarily adults and observed increased grass pollen concentrations to be associated with middle–small airway changes 2–3 days after exposure, as reflected by the FEV 1 /FVC ratio and FEF 25–75% , respectively [ 29 ]. Similarly, Lambert et al [ 82 ] observed a reduction in FEV 1 and FVC with increasing concentrations of tree pollen at lag 1 and lag 3 in 8-year-old ‘high-risk’ children residing in Sydney, Australia [ 82 ]. The same authors investigated similar relationships in adolescents of the GINIplus and LISA cohorts in Germany, but observed the association to be present only in those who were pollen sensitised [ 30 ].…”
Section: Short-term Impact Of Pollen On Adverse Respiratory Outcomesmentioning
confidence: 99%
“…Other work covered the issue of product availability for venom immunotherapy in the UK, 115 epidemiology of allergic and respiratory disease 116‐119 , 120 , 121 occupational allergies, 122‐124 advances in allergy diagnostics 125‐133 , 134 , 135 , 136 , animal model work 137 138 , 139 , 140 , 141 , investigation of infant airway epithelium, 142 a possible association between tree pollen exposure and reduced lung function 143 and evaluations of allergy service delivery 144‐147 …”
Section: Other Areas Of Interestmentioning
confidence: 99%